Assessment of Costs Associated with Deer–Vehicle Collisions: Human Death and Injury, Vehicle Damage, and Deer Loss - John A. Bissonette; Christine A. Kassar; Lawrence J. Cook (Human-Wildlife Interactions, 2017)
Collisions between large vertebrates and vehicles along roadways are an increasing concern, not only because of ecological consequences, but also because of associated economic and social costs. We used a large-scale, long-term data set comprising several databases from Utah to summarize and analyze these costs. The overall cost for 13,020 collisions from 1996 to 2001 in Utah was approximately $45,175,454, resulting in an estimated average per year cost of about $7,529,242 and a mean collision cost of $3,470. These figures include human fatality costs of $24 million (53% of total costs); vehicle damage costs of $18 million (39%); loss of deer, valued at $2.7 million (6%); and human injury costs of $1 million (2%). Cost-benefit analyses have shown that mitigation efforts, which are prioritized based on road-kill data, can produce positive net economic gains and also increase driver safety.